2012
DOI: 10.1186/1471-2334-12-67
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial infections in Lilongwe, Malawi: aetiology and antibiotic resistance

Abstract: BackgroundLife-threatening infections present major challenges for health systems in Malawi and the developing world because routine microbiologic culture and sensitivity testing are not performed due to lack of capacity. Use of empirical antimicrobial therapy without regular microbiologic surveillance is unable to provide adequate treatment in the face of emerging antimicrobial resistance. This study was conducted to determine antimicrobial susceptibility patterns in order to inform treatment choices and gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
36
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 19 publications
14
36
6
Order By: Relevance
“…An earlier study in India has observed that the infection rate due to Cryptococcus neoformans was 2.93% to 3.13%, and it is lower than our finding (4%) [8]. A study conducted in Malawi had significantly higher frequency of C. neoformans (39.1%) and this high prevalence was likely related to prevalence of HIV infection in their patients and which is different in our study [9], where up to twothirds of patients had neurosurgical procedures.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…An earlier study in India has observed that the infection rate due to Cryptococcus neoformans was 2.93% to 3.13%, and it is lower than our finding (4%) [8]. A study conducted in Malawi had significantly higher frequency of C. neoformans (39.1%) and this high prevalence was likely related to prevalence of HIV infection in their patients and which is different in our study [9], where up to twothirds of patients had neurosurgical procedures.…”
Section: Discussioncontrasting
confidence: 56%
“…The development of many drug-resistant organisms, such as carbapenemresistant and methicillin/oxacillin-resistant strains, and extended-spectrum beta-lactamase (ESBL) producing bacteria may reflect the changing trend of pathogens and their antimicrobial susceptibility pattern [9,10]. Therefore, microbiological surveillance is important to identify the common pathogens and their antimicrobial susceptibility patterns in order to select the rational empirical antimicrobial therapy based on regional and national data to reduce the emergence of resistant organisms [8,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Actinobacteria were also prevalent in bird manure, water, and fish fecal samples and are generally associated with high antibiotic resistance genes, particularly MFS transporters (Forsberg et al, 2014). Lastly, fluoroquinolone antibiotics have been used to treat Malaria for many decades (Divo, Sartorelli, Patton, & Bia, 1988), but was replaced in 1993 by other drugs (Laufer et al, 2006), although this class of antibiotics is still widely used to treat a variety of gram negative bacterial infections as ciprofloxacin (Makoka et al, 2012). Antibiotics are used broadly in hospital and other rural clinics in Malawi, while agriculture use is not well documented.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have suggested a higher proportion of S. aureus in urinary tract infections: 6.3–13.9% of urinary tract infections are caused by S. aureus in Senegal , Ghana , and Nigeria , as compared with 1.06% in Europe and Brazil . In general, S. aureus is a major pathogen in bloodstream infections (9.5–39.0%), skin and soft tissue infections (62.8–90.0%), ear, nose and throat infections (16.7–29.0%), and surgical site infections (20.4–32.0%) .…”
Section: Epidemiology Of S Aureus Colonizationmentioning
confidence: 99%